The effectiveness of laboratory use in supporting biology practicums in high schools throughout Manokwari Regency - Frabun, Ronal F.; Iwan, Iwan; Wambrauw, Hengky L. (Inornatus: Biology Education Journal, 2018)
This study aims to analyze the effectiveness of laboratory used in practices biology field at Two Senior high school, called SMA in Manokwari regency. This study is a qualitative-descriptive. The data collected by observation sheets, or quistionnaries. thatÂ  answered by two teachers and six students. The result showed that SMA Negeri 1 Prafi effectivelly in used laboratory for doing practices or effectively categorized by 74,72% and SMA Katolik Villanova reached up and average 67.56% means to support the laboratory Experient or categorized as effective. While obstacles of the Two school still high reached up 80%, while the percentage of the standardized laboratory equipments are familier spread from 49%-51%.Â